Analysis of Gender Discrimination in Precious Movie - Lestari, Noni Dwinka (UNIVED Press, 2025)
This research discusses gender discrimination in the “Precious” movie. This research has two objectives. (1) To find the forms of gender discrimination in Precious movie. (2) To investigate the factors cause gender discrimination in the Precious movie. This study used descriptive qualitative method. This is related to data descriptions in the form of conversations and descriptions of actions in the his. The analysis in this research uses analysis from spreadlay and theory from Zulhayatin and Relawati. The research's findings demonstrate that 3 of the 5 forms of gender discrimination namely violence, stereotypes, and marginalization were discovered. Additionally, the rationality factor and the patriarchy factor are the two causes of the gender discrimination that Precious experienced in the “Precious” movie. Based on the research that has been completed, there are 7 data sentences or actions that contain gender discrimination experienced by the character Precious in the “Precious” movie. In accordance with the data, researcher found that 5 data were caused by patriarchy factors, and 2 data were caused by rationality factors.